Young people's beliefs about the risk of bowel cancer and its link with physical activity. Issue 3 (17th April 2017) - Newby, Katie V.; Cook, Chloe; Meisel, Susanne F.; Webb, Thomas L.; Fisher, Bernadette; Fisher, Abi
Abstract : Objectives: The primary objective was to explore young people's risk appraisals of bowel cancer, including whether they had a coherent understanding of the protective effects of physical activity (PA). A secondary objective was to examine whether the illness risk representations (IRRs) framework could be used to understand beliefs underlying bowel cancer risk appraisals. Design: Qualitative. Methods: Framework analysis of semi‐structured interviews with 19 people aged 14–17 years. Results: Participants judged their risk of getting bowel cancer as low. This was based on a lack of family history of cancer and their current lifestyle behaviours, which were viewed as having a protective effect, or because they planned on making change to their lifestyle in the future when disease risk became more relevant. Participants were not aware of, and struggled to understand, the link between PA and bowel cancer. They also lacked knowledge of the effects of, or treatments for, bowel cancer. Beliefs underlying judgements about the risk of bowel cancer fitted the IRR framework reasonably well. Conclusions: The present research suggests that interventions designed to increase PA with a view to reducing the risk of bowel cancer should aim to make the future risk of bowel cancer feel more tangible, help young people to understand the full range of consequences, explain how and why preventative behaviours such as PA are effective in reducing risk, and emphasize that the typical late presentation of symptoms, and therefore investigation by health care services, reduces treatability. Statement of contribution What is already known on this subject? Physical activity (PA) performed throughout the lifespan can have a protective effect on bowel cancer, but levels of PA are low among young people. Changing beliefs about the risk of getting bowel cancer may be a useful strategy in motivating PA. What does this study add? Increased understanding of how young people think about bowel cancer and the relationship between PA and cancer. Identification of strategies for increasing young adults' appraisals of the likelihood and severity of bowel cancer. Evidence to support the validity of illness risk representations framework.